1987
DOI: 10.1159/000298842
|View full text |Cite
|
Sign up to set email alerts
|

Placental Proteins in Peripheral Blood and Tissues of Ectopic Pregnancies

Abstract: Circulating human chorionic gonadotrophin (hCG), Schwangerschaftsprotein 1 (SP-1) and pregnancy-associated plasma protein A (PAPP-A) were examined in 10 women with ectopic gestation in relation to distribution and intensity of staining for these molecules using immunohistochemical techniques applied to matched trophoblastic and decidualized endometrial tissues. All 10 women revealed strong staining for hCG and SP-1 in the syncytiotrophoblast, which was apparently unrelated to maternal levels of hCG and SP-1, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
(7 reference statements)
0
14
1
Order By: Relevance
“…Despite the fact that with this test, no distinction can be made between ectopic pregnancies and intra-uterine abortions, PAPP-A is certainly an excellent parameter by which to monitor postimplantation viability of embryos. In the present study, and in contrast to other studies (Grudzinskas et al, 1984;Sjoberg, 1987;Tornehave et al, 1987), PAPP-A levels were depressed in ectopic pregnancies but never below the sensitivity of the assay and were even measurable in non-pregnant women. As reported recently (Bischof and Meisser, 1989), this difference is due to the immunological heterogeneity of PAPP-A and to the fact that we use EDTA plasma samples and standards.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that with this test, no distinction can be made between ectopic pregnancies and intra-uterine abortions, PAPP-A is certainly an excellent parameter by which to monitor postimplantation viability of embryos. In the present study, and in contrast to other studies (Grudzinskas et al, 1984;Sjoberg, 1987;Tornehave et al, 1987), PAPP-A levels were depressed in ectopic pregnancies but never below the sensitivity of the assay and were even measurable in non-pregnant women. As reported recently (Bischof and Meisser, 1989), this difference is due to the immunological heterogeneity of PAPP-A and to the fact that we use EDTA plasma samples and standards.…”
Section: Discussioncontrasting
confidence: 99%
“…In first-trimester pregnancies with an ultrasonically proven live fetus, low PAPP-A levels had a 49% predictive value of fetal demise with a sensitivity of 89% (Westergaard, 1987). In ectopic pregnancies, most authors found very depressed (<10th centile) or even unmeasurable concentrations of PAPP-A (Grudzinskas et al, 1984;Sjoberg, 1987;Tornehave et al, 1987) whereas in a similar study with a different design, we found only slightly depressed PAPP-A levels (Bischof et al, 1983).…”
Section: Introductionmentioning
confidence: 46%
See 1 more Smart Citation
“…However, in some cases, serum SP-1 was within the normal range (nZ10) and the pregnancy still had an abnormal outcome. Serum SP-1 concentrations do tend to be lower in tubal ectopic pregnancy (Tornehave et al 1987), but again larger studies have confirmed that there is poor discrimination between tubal ectopic pregnancy (nZ32) and spontaneous abortion (nZ42; Witt et al 1990). In tubal ectopic pregnancy, serial SP-1 measurements reached a plateau, while in ongoing pregnancy they continue to increase (Mantzavinos et al 1991, Mueller et al 2004) and the differences were most marked after 7 weeks of gestation.…”
Section: Pregnancy-associated Plasma Protein-amentioning
confidence: 97%
“…EGP is also homologous to placental protein 12, which is secreted by the endometrium into the amniotic fluid during the first trimester-of pregnancy (28,32,33). Interestingly, many types of tumors express high levels of placental protein 12 (34,35).…”
mentioning
confidence: 99%